A Precious‐Metal‐Free Regenerative Fuel Cell for Storing Renewable Electricity. Issue 12 (31st July 2013) - Desmond Ng, Jia Wei; Gorlin, Yelena; Hatsukade, Toru; Jaramillo, Thomas F.
<x xml:space="preserve">Abstract</x> A low‐temperature, precious‐metal‐free alkaline anion exchange membrane unitized regenerative fuel cell is developed. The prototype device obtains round trip efficiencies of 34–40% at 10 mA cm−2, with a peak power density of 17 mW cm−2 in fuel cell mode. This opens up new possibilities for enabling cost‐effective and widespread deployment of renewable electricity. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>